2018
DOI: 10.1002/jum.14551
|View full text |Cite
|
Sign up to set email alerts
|

Telepresent Focused Assessment With Sonography for Trauma Examination Training Versus Traditional Training for Medical Students: A Simulation‐Based Pilot Study

Abstract: Telepresent education is a viable option for teaching the FAST examination to medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 16 publications
0
57
1
Order By: Relevance
“…Low-cost tele-ultrasound setups such as multiple-fixed cameras, audio in conjunction with a live ultrasound stream, and smartphones have been explored as means of ultrasound training [4]. Poland et al 2018 demonstrated that tele-ultrasound has a place in medical student education as an effective means of learning new sonography skills [15,16]. Therein lies an opportunity to build upon these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Low-cost tele-ultrasound setups such as multiple-fixed cameras, audio in conjunction with a live ultrasound stream, and smartphones have been explored as means of ultrasound training [4]. Poland et al 2018 demonstrated that tele-ultrasound has a place in medical student education as an effective means of learning new sonography skills [15,16]. Therein lies an opportunity to build upon these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise another study reported a significant increase both in the mean number of correct answers on the 26-item hypertension knowledge test (from 13.11 to 17.44, p < .01) and on the 7item hypertension management self-efficacy scale (from 4.68 to 5.41, p < .01) among the primary care practitioners in the intervention group in Chicago's south side [10] . The positive outcome in the current study could be attributed to both the informative didactics delivered by experts in the concerned fields, and practical, evidence-based learning through the medium of case presentations by the participants [11].Apart from this, the time designated during each session for questions and interaction among the participants and the experts facilitated further knowledge enhancement. [11] Poland et al [11] , Ciullo et al [12], and Panait et al [13] compared in-person training and tele mentoring of medical students in different medical procedures like the focused assessment with sonography for trauma (FAST) examination, mechanical ventilation, and laparoscopy respectively, and reported almost similar efficacy of both and found the benefit of both the training methodologies comparable.…”
Section: Discussionmentioning
confidence: 67%
“…The positive outcome in the current study could be attributed to both the informative didactics delivered by experts in the concerned fields, and practical, evidence-based learning through the medium of case presentations by the participants [11].Apart from this, the time designated during each session for questions and interaction among the participants and the experts facilitated further knowledge enhancement. [11] Poland et al [11] , Ciullo et al [12], and Panait et al [13] compared in-person training and tele mentoring of medical students in different medical procedures like the focused assessment with sonography for trauma (FAST) examination, mechanical ventilation, and laparoscopy respectively, and reported almost similar efficacy of both and found the benefit of both the training methodologies comparable. Moreover, a recent study from a developing county stated, 65.41% healthcare workers used e-learning platforms for upgrading their knowledge during COVID-19, suggesting increased preference towards online training as it saves travel during pandemic without compromising learning [14].…”
Section: Discussionmentioning
confidence: 67%
“…While some current research has focused on the effects of remote teaching and assessment on student learning and achievement, little research has examined student perceptions or preferences regarding the two modalities of teaching and evaluation. 15 This study addresses this knowledge gap by assessing pharmacy student perceptions and preferences of video versus in-person evaluations.…”
Section: A J P Ementioning
confidence: 99%